Tuberculous Knee Joint - A Case Report - Arvin Raj, Goonasegaran; Lik Han, Ong; Faris, Kamaruddin (MALAYSIAN ORTHOPAEDIC ASSOCIATION, 2016)
Tuberculosis is an ancient disease that is still a major morbidity worlwide. Along with the increase in prevalence of pulmonary tuberculosis, skeletal tuberculosis seems to be on the rise too. The complication of joint related tuberculosis can be very disabling and may impede the function of an individual if left untreated.The incidence of extrapulmonary tuberculosis is ranging from 2- 20% and in Malaysia it represents 10% of cases, of which skeletal tuberculosis may range from 1-20% ofall extrapulmonary tuberculosis. In Sarawak, osteoarticular tuberculosis has been encountered in the spine, hip, knee, elbow and wrist.